Effects of pyrethroid pesticide cis-bifenthrin on lipogenesis in hepatic cell line. (June 2018) - Xiang, Dandan; Chu, Tianyi; Li, Meng; Wang, Qiangwei; Zhu, Guonian
Abstract: Mounting evidence suggests there is a link between exposure to synthetic pyrethroids (SPs) and the development of obesity. The information presented in this study suggests that cis -bifenthrin ( cis -BF) could activate pregnane X receptor (PXR) mediated pathway and lead to the lipid accumulation of human hepatoma (HepG2) cells. Cells were incubated in the control or different concentrations of cis -BF for 24 h. The 1 × 10 −7  M and 1 × 10 −6  M cis -BF exposure were found to induce cellular triglyceride (TG) accumulation significantly. This phenomenon was further supported by Oil Red O Staining assay. The cis -BF exposure caused upregulation of PXR gene and protein. Correspondingly, we also observed the increased expression of downstream genes involved in lipid formation and the inhibition of the expression of β-oxidation. As chiral pesticide， cis -BF was further conformed to behave enantioselectivity in the lipid metabolism. Rather than 1 R - cis -BF, HepG2 cells incubated with 1 S - cis -BF exhibited a significant TG accumulation. 1 S - cis -BF also showed a higher binding level, of which the KD value was 9.184 × 10 −8  M in the SPR assay, compared with 1 R - cis -BF (3.463 × 10 −6  M). In addition, the molecular docking simulation analyses correlated well with the KD values measured by the SPR, indicating that 1 S - cis -BF showed a better binding affinity with PXR. The results in this study also elucidates the differences between the two enantiomers of pyrethroid-induced toxicity in lipid metabolism of non-target organism. Graphical abstract: Image 1 Highlights: Cis -BF exposure could result in lipid accumulation in HepG2 cells. Cis -BF behaves enantioselective effects in the lipid metabolism. Cis -BF increases synthesis and decreases metabolism of lipid by activating PXR.